2016
DOI: 10.1097/mao.0000000000001160
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes for Single Modality Management of Glomus Jugulare Tumors With Stereotactic Radiosurgery

Abstract: Objectives The objectives were to evaluate the audiological outcomes, response of symptoms, and response of tumor volume in patients with glomus jugulare tumors treated solely with single fraction gamma knife radiosurgery. Study Design Single institution retrospective review. Setting Academic, tertiary referral center. Patients The diagnosis code for glomus jugulare was used to identify patients. Only those who underwent gamma knife radiosurgery were included. Those previously treated with any modality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…A total of 29 studies have been identified 9‐37 . One study was a multicenter trial with 132 patients and was counted as a separate publication even though parts of the data had already been reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 29 studies have been identified 9‐37 . One study was a multicenter trial with 132 patients and was counted as a separate publication even though parts of the data had already been reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies met the inclusion/exclusion criteria (Table 1) and were analyzed (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). These studies contained 511 patients studied during 1988 to 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Radiosurgery primarily controls growth of the tumor and may reduce symptoms as a primary or secondary modality. 9 , 10 Resection is another treatment option, particularly if there is existing CN compression with associated neurological deficit. Embolization has been used preoperatively since the 1980s to reduce intraoperative blood loss, 11 although it is not curative by itself 12 and may be associated with higher risk of postoperative CN deficits.…”
Section: Discussionmentioning
confidence: 99%